2007
DOI: 10.1115/1.2437218
|View full text |Cite
|
Sign up to set email alerts
|

PIV Maps of Tip Leakage and Secondary Flow Fields on a Low-Speed Turbine Blade Cascade With Moving End Wall

Abstract: New, detailed flow field measurements are presented for a very large low-speed cascade representative of a high-pressure turbine rotor blade with turning of 110deg and blade chord of 1.0m. Data were obtained for tip leakage and passage secondary flow at a Reynolds number of 4.0×105, based on exit velocity and blade axial chord. Tip clearance levels ranged from 0% to 1.68% of blade span (0% to 3% of blade chord). Particle image velocimetry was used to obtain flow field maps of several planes parallel to the tip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Some studies found the relative end-wall motion had a large effect on the thermal performance of the blade tip, including Zhou et al [20], Palafox et al [21], and Rhee and Cho [22]. On the blade profile used in this paper, Krishnababu et al [23] found that the effects of end-wall motion on the thermal performance of the uncooled flat tip and cavity tip were marginal.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Some studies found the relative end-wall motion had a large effect on the thermal performance of the blade tip, including Zhou et al [20], Palafox et al [21], and Rhee and Cho [22]. On the blade profile used in this paper, Krishnababu et al [23] found that the effects of end-wall motion on the thermal performance of the uncooled flat tip and cavity tip were marginal.…”
mentioning
confidence: 68%
“…It should be noted that the effects of end-wall motion were found to have a significant effect on the thermal performance of the tip in other studies [20,21], probably because of the different blade profiles used.…”
Section: Effects Of End-wall Motionmentioning
confidence: 81%
“…Muthanna and Devenport [18] have summarized the extensive research of the flow in the passage and immediate downstream of compressor linear cascade and axial pump. Efforts to understand the physics of this complex flow due to the tip gap are continuing [19].…”
Section: Introductionmentioning
confidence: 99%
“…In modern high load turbines, the loss induced by tip clearance leakage flow is remarkable. A number of investigations on tip clearance leakage flow have been performed by many researchers [9][10][11][12][13][14][15][16][17][18][19][20][21][22] to decrease the flow loss. Farokhi [9] analyzed the tip clearance loss in an axial flow turbine and proposed a model that accounts for tip pressure loading, relative wall motion and stage characteristics.…”
mentioning
confidence: 99%
“…The local measurements of the heat transfer coefficient and pressure coefficient on the tip and near tip region of a generic turbine blade made by Newton et al [19] revealed that the flow through the plain gap was dominated by flow separation at the pressure-side edge and that the highest levels of heat transfer were located where the flow reattaches on the tip surface. Particle image velocimetry (PIV) was used by Palafox et al [20] to obtain flow field maps of several planes parallel to the tip surface within the tip gap, and adjacent passage flow. The dominant effect of the tip leakage flow on the tip end-wall secondary flow was revealed.…”
mentioning
confidence: 99%